2017
DOI: 10.1021/acsmacrolett.7b00064
|View full text |Cite
|
Sign up to set email alerts
|

Fabrication of Multicomponent Multivesicular Peptidoliposomes and Their Directed Cytoplasmic Delivery

Abstract: A novel self-assembly strategy for the formation of multicomponent and multicompartment vesicles via the hierarchical assembly of the cyclic peptide and lipid building blocks is reported. The primary driving force underlying the formation of dual-component (i.e., peptide and lipid) heteromultivesicular vesicles (hMVVs) is the differential thermostability between the supramolecular building blocks. Furthermore, the combination of the differential thermostability and charge-based separation further enables the f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 27 publications
0
6
0
Order By: Relevance
“…In contrast, spherical and cylindrical micelles can employ only encapsulation mechanisms for drug loading. In particular, the loading of drugs by the encapsulation mechanism is especially suitable for polymers and peptides because they can form more robust nanoparticles than lipids [ 10 , 11 ]. Given the usefulness of vesicles in drug delivery and the multifunctionality of peptides as supramolecular building blocks, we intend to design and fabricate peptidesomes that can become highly functional nanodrugs in vivo .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In contrast, spherical and cylindrical micelles can employ only encapsulation mechanisms for drug loading. In particular, the loading of drugs by the encapsulation mechanism is especially suitable for polymers and peptides because they can form more robust nanoparticles than lipids [ 10 , 11 ]. Given the usefulness of vesicles in drug delivery and the multifunctionality of peptides as supramolecular building blocks, we intend to design and fabricate peptidesomes that can become highly functional nanodrugs in vivo .…”
Section: Resultsmentioning
confidence: 99%
“…First, peptide building blocks should have a strong propensity to form vesicles rather than other morphologies, which would facilitate performing feedback control of the SPN nanostructural properties by modifying the chemical structures of the peptides. We elected to use cyclic peptides as building blocks because peptides that are both cyclic and amphiphilic have shown a strong tendency to self-assemble into vesicles (peptidesomes) [ 11 ]. Second, the hydrophilic segment of the building blocks would contain a large proportion of arginine residues for the efficient intracellular translocation of SPNs.…”
Section: Resultsmentioning
confidence: 99%
“…(C) Fabrication of the quadruple-hMVV. Reprinted with permission from ref . Copyright 2017 American Chemical Society.…”
Section: Programmed Delivery and Biological Applications Of Mcpsmentioning
confidence: 99%
“…Contrary to concentric multiwalled vesicles, the walls of the obtained onion-like polymersomes separated by water channels, exhibiting higher drug-loading capacity and stepwise drug-releasing behavior via hydrolytic degradation of the PCL membrane compared to that observed with the single-walled analogue. Moreover, Lim et al 129 reported a self-assembly method for preparing multicomponent and multicompartment polymersomes by multistage selfassembly of peptides and lipid structural units (Figure 20A). The differences of the thermal stability of the building blocks were attributed to the formation of two-component (i.e., peptide and lipid) heteropolyvesicles (hMVVs).…”
Section: Programmed Delivery and Biological Applications Of Mcpsmentioning
confidence: 99%
See 1 more Smart Citation